A Study on the association between plasma glucose, glycosylated hemoglobin and macro metals Calcium and Magnesium in Diabetes Mellitus - madhu, gandhi; tejaram, venkateswari; selvanayagam, Dr.swaminathan; shanmugam, Rajeshwari (Journal of Experimental Sciences, 2013)
Abstract To find out the association between Fasting plasma glucose, glycosylated Hemoglobin to macro metals calcium and magnesium in a randomly selected 50 patients ( both diabetic and non diabetic) attending the MHC. Comparison of both men and women (men= 26, women=24) in the age group of 23 to 72 years were enrolled, Fasting plasma glucose, glycoHb, calcium and magnesium were measured using the fasting blood samples. The parameters were then subjected to statistical analysis to find out the relation between any two analytes. Results of paired t tests with a p of <0.01 was considered significant and p<0.001 were considered highly significant to conclude an association between the analytes studied. This study has proved beyond doubt that calcium and magnesium are indeed involved in diabetes mellitus both in its regulation and glucose metabolism. As the study was carried out during a short period of 1 Month, we were unable to indicate control subjects but purely worked out to find the association between FPG, Glycosylated hemoglobin, calcium and magnesium. The study recommends that along with glucose and Glycosylated hemoglobin, calcium and magnesium assays too should be carried out as additional parameters in the evolution of diabetes mellitus.Based on this study we strongly recommend that further research should be carried out to establish the role of calcium and magnesium especially red cell calcium and magnesium and diabetes mellitus.